Environmental radioactivity of cryoconite collected at the Flade Isblink ice cap (NE Greenland) ... - Beard, Dylan; Baccolo, Giovanni; Clason, Caroline C; Millward, Geoffrey E; Łokas, Edyta; Rangecroft, Sally; Sala, Dariusz; Wachniew, Przemysław; Blake, William H (PANGAEA, 2024)
This database is about the environmental radioactivity analyzed in cryoconite samples collected on the surface of the Flade Isblink ice cap, in NE Greenland.46 samples of cryoconite were collected on 2nd and 3rd of August 2022 on the surface of the glacier. Moreover, 2 samples from riverine sediments were collected as well in the surrounding of the glacier, one from a glacial river, one from a non glacial river. The environmental radioactivity was measured through gamma and alpha spectrometry, and atomic mass spectrometry. This allowed to measure a number of radionuclides, including artificial and natural species. For plutonium isotopes it was also possible to analyze the atomic mass ratio between isotopes 239 and 240. Also Loss of Ignition and carbonate content were measured. Collection took place in an area of the glacier with a surface of about 0.25 km², in the northern part of Flade Isblink. Cryoconite was collected for investigating the occurrence and distribution of environmental radioactivity in the ...